2022
DOI: 10.3389/fmolb.2022.982593
|View full text |Cite
|
Sign up to set email alerts
|

Targeting extracellular Hsp90: A unique frontier against cancer

Abstract: The molecular chaperone Heat Shock Protein-90 (Hsp90) is known to interact with over 300 client proteins as well as regulatory factors (eg. nucleotide and proteins) that facilitate execution of its role as a chaperone and, ultimately, client protein activation. Hsp90 associates transiently with these molecular modulators during an eventful chaperone cycle, resulting in acquisition of flexible structural conformations, perfectly customized to the needs of each one of its client proteins. Due to the plethora and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 139 publications
(204 reference statements)
0
8
0
Order By: Relevance
“…Some of these upregulated genes can function intracellularly to activate macrophages or be released to the extracellular space to amplify inflammatory activities through other cells. 29 31 We observed that these mutations casted similar impacts on both the CCR2+ and CCR2− macrophages, suggesting a pan-immune activation associated with the mutations.…”
Section: Discussionmentioning
confidence: 70%
“…Some of these upregulated genes can function intracellularly to activate macrophages or be released to the extracellular space to amplify inflammatory activities through other cells. 29 31 We observed that these mutations casted similar impacts on both the CCR2+ and CCR2− macrophages, suggesting a pan-immune activation associated with the mutations.…”
Section: Discussionmentioning
confidence: 70%
“…Similar immune activation phenotypes were shown in the heart macrophages with additional chemokines (Figure 2A-D) upregulated in the carriers. Many of these upregulated genes can function intracellularly to activate macrophages or be released to the extracellular space to amplify inflammatory activities through other cells 2628 . On the other hand, our data also showed distinctive impacts of CHIP on plaque and cardiac macrophage functions and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To understand whether different clinical attributes could underlie differences in survival across CM patients, we assessed several melanoma characteristics that are dependent on the PN: pigmentation, rate of subsequent metastasis, drug response and tumour thickness across our patient sub-groups 21,22 wherever data was available. We found that in primary cohorts, samples in group A had higher pigmentation scores and lower subsequent metastasis than those in group B, as well as a trend towards reduced tumour thickness (Supplementary Fig.…”
Section: Sub-groups Are Distinguished By a Transcriptional Shift From...mentioning
confidence: 99%